Studi Komparasi Pemeriksaan MRI 0,5 Tesla Terhadap EEG Skalp dan Evaluasi Hasil Operasi Berdasarkan Kriteria Engel pada Epilepsi Mesial Temporal Sclerosis - Nurdopo Baskoro; Hermina Sukmaningtyas; Abubakar Abubakar (MEDIA MEDIKA INDONESIANA, 2009)
Comparative study of MRI 0,5 Tesla result with scalp ECG and evaluation of surgery result based on Engel classification among patient with mesial temporal sclerosis epilepsy.Background: Accurate preoperative localization of the epileptic is important in the intraoperative localization of lesion which ultimately will control the postoperative seizures.Purpose: To investigate the association among routine scalp electroencephalographic (EEG), Magnetic Resonance Imaging (MRI) 0.5 Tesla and Surgical outcome using Engel’s criteria in Mesial Temporal Sclerosis (MTS).Methods: This study used is an analitical descriptive study with cross sectional design. Correlation between EEG and MRI was analized using the Kappa and MRI findings with operative outcome was analized using the Spearmann. Forty seven patients with intractable Epilepsy who underwent temporal lobe lobectomy between 2000 and 2007 were the subjects of the study.Results: Routine scalp EEG and MRI findings revealed that the focus were the mostly temporal lobe epileptiform in the right side. Comparing the EEG foci with MRI lesion, the study revealed same location of foci in the right side (42.6% vs 61.7%), in the left side (27.7% vs 27.7%), bilateral (14.9% vs 2.1%) and normal (14.9% vs 8.5%). The correlation of  lateralization of foci between EEG findings and MRI lesion is significan. There was association between the MRI 0.5 Tesla findings and operative outcome (r=0.352, p=0.015). All patients after surgery showed I-III Engel’s classification.Conclusions: Result of MRI 0.5 Tesla gives slight agreement with scalp ECG result but is associated with the operation outcome based on Engel classification.Keyword: MTS, EEG, MRI 0.5 T, Engel’s criteriaABSTRAKLatar belakang: Menentukan lokalisasi fokus epilepsi secara akurat sangat membantu dalam melokalisasi lesi intraoperasi yang pada akhirnya dapat mengkontrol serangan kejang pasca operasi.Tujuan: Untuk mencari hubungan antara pemeriksaan rutin elektroensefalografi (EEG) skalp dan MRI 0,5 Tesla dan hasil operasi berdasarkan kriteria Engel pada Mesial Temporal Sclerosis.Metode: Jenis penelitian ini menggunakan studi deskriptif analitik dengan desain Cross Sectional. Hubungan antara EEG dan MRI dilakukan analisis dengan Kappa dan antara temuan MRI dan hasil operasi dilakukan analisis dengan Uji korelasi Spearman. Dievaluasi sebanyak 47 pasien dengan epilepsi intraktabel yang telah dilakukan operasi lobektomi temporal antara tahun 2000- 2007.Hasil: Dari pemeriksaan EEG scalp dan MRI didapatkan fokus epilepsi lobus temporalis lebih banyak di sisi kanan. Perbandingan lokasi fokus berdasarkan EEG dan MRI adalah lokasi yang sama pada sisi kanan (42,6% vs 61,7%), pada sisi kiri (27,7% vs 27,7%), bilateral (14,9% vs 2,1%) dan normal (14,9% vs 8,5%). Lateralisasi fokus antara pemeriksaan EEG dan MRI menunjukkan hubungan yang bermakna. Ada hubungan antara pemeriksaan MRI 0,5 Tesla dan hasil operasi (r=0,352, p=0,015). Pasca operasi,semua pasien termasuk dalam kriteria Engel I-III.Simpulan: MRI 0,5 Tesla menunjukkan kesesuaian yang rendah dengan hasil EEG, namun berkorelasi dengan temuan hasil operasi.